1997
DOI: 10.1007/s002239900293
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Bone Turnover in Camurati–Engelmann Disease: A Report on Four Cases in One Family

Abstract: Moderate increases in "classical" biochemical markers of bone turnover have been described only in some patients with Camurati-Engelmann disease. However, the determination of the following "new" markers has not been previously performed: serum osteocalcin (BGP), bone alkaline phosphatase (BAP), carboxyterminal propeptide of type I procollagen (PICP), aminoterminal propeptide of type I procollagen (PINP), tartrate-resistant acid phosphatase (TRAP), telopeptide carboxyterminal of type I collagen (ICTP), urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…Although CED is characterized by a net increase in bone mass in some regions of the skeleton, bone resorption is also increased, as reflected by biochemical markers of bone resorption that are increased 3-to 10-fold above the normal range in affected patients (11). This indicates that the activating mutations of TGF␤1 that cause CED result in a state of increased bone turnover, rather than just an increase in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although CED is characterized by a net increase in bone mass in some regions of the skeleton, bone resorption is also increased, as reflected by biochemical markers of bone resorption that are increased 3-to 10-fold above the normal range in affected patients (11). This indicates that the activating mutations of TGF␤1 that cause CED result in a state of increased bone turnover, rather than just an increase in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations do not include fibrosis or aneurysm, and no evidence for increased TGF-b signaling has been described in the aortic wall or other tissues, suggesting that these mutations have tissue-specific effects on TGF-b activity. It appears that patients with CED have increased rates of bone resorption as well as bone formation, with the overall balance shifted toward bone formation, possibly because of increased proliferation of osteoblasts (Hernandez et al 1997;Saito et al 2001;McGowan et al 2003). CED can be successfully treated with glucocorticosteroids, which decrease proliferation, maturation and ECM synthesis in osteoblasts and osteocytes, and also increase the rate of apoptosis of these cells, thus resulting in a net decrease in bone mass (Low et al 1985;Naveh et al 1985).…”
Section: Gain Of Bone Mass In Camurati -Engelmann Diseasementioning
confidence: 99%
“…CED is a rare autosomal dominant genetic disorder characterized by hyperostosis and sclerosis, especially affecting the diaphysis of long bones. Clinically, CED is characterized by radiological osteosclerosis, but affected patients also have increased markers of bone resorption, suggesting that bone resorption is elevated as well as bone formation (Hernandez et al 1997). The causal gene for CED was mapped to chromosome 19q13 by linkage analysis Janssens et al 2000b), and then mutations in TGFB1 were identified as a cause using a positional candidate approach (Janssens et al 2000a;Kinoshita et al 2000).…”
Section: Transforming Growth Factor Tgf-␤1mentioning
confidence: 99%